Genome Editing to Enhance Disease Resistance in Livestock - Laohasatian, Teerajet; Manatrinon, Supawadee; Seritrakul, Pawat (Journal of Mahanakorn Veterinary Medicine, 2022)
Animal diseases significantly impact livestock production, agriculture, the economy, as well as exposing human to foodborne illnesses that originate from animals. Recently, potential new techniques have emerged that could efficiently prevent and treat animal diseases, one of which is genome editing, which is a technique that can alter genetic information by inserting or removing parts of target genes. Currently, the most widely used genome editing techniques include Zinc-finger nucleases (ZFNs), Transcription activator-like effector nucleases (TALENs), and Clustered regulatory interspaced short palindromic repeats (CRISPRs). This article reviews genome editing techniques (ZFNs, TALENs, and CRISPRs) that have been employed for editing the genomes of livestock. Overall, genome editing has been shown to increase disease resistance, either by removing the causative part of the genes or by replacing them with a resistance cassette, thus enhancing disease resistance in livestock.